(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Bruxism is defined as “diurnal or nocturnal parafunctional activity including clenching, bracing, gnashing, and grinding of the teeth.” The etiology of bruxism is unclear, but the condition has been associated with stress, occlusal disorders, allergies, and sleep positioning. The aetio-pathophysiology is still unclear. SB (Sleep Bruxism) has been associated with tooth interference, psychosocial and environmental factors, brain transmitters, and basal ganglia dysfunction. It is been reported that Sleep bruxism during all sleep stages, others observed the majority of bruxe episodes during light sleep and REM and are often associated with arousal transients. There is no specific treatment for sleep bruxism but each subject has to be individually evaluated and treated. Three management alternatives are used: dental, pharmacological, and psycho behavioural. A 69-year-old man came to OPD of VPSV Ayurveda College Hospital, complaining that he has been grinding his teeth and making sounds while sleeping for the last 15 years. The noise he created caused his wife’s sleep to be disturbed as well. So she constantly gave him the blame. They noted that the patient’s tendency to grind his teeth worsened whenever he became upset or overworked. The patient had been given Aswagandha Churna (3gm), Jatamansi Churna (2gm), Aparajita churna (2gm) 2 times after food with warm water and Mahapaishacika ghrta 10ml at night for 3 weeks and also by considering the stress factor hypnotherapy was given 4 sittings on every 3rd day. The patient had good improvement in the Perceived Stress Scale, it reduced from 20 to 11. After three weeks of treatment, sleep bruxism was completely cured and the patient was asymptomatic during the follow-up period also.